A biomimetic injectable chitosan/alginate hydrogel biocopmosites encapsulating selenium- folic acid nanoparticles for regeneration of spinal cord injury: An in vitro study - Farzan, Mahan; Soleimannejad, Mostafa; Shariat, Saeedeh; Heidari Sureshjani, Mina; Gholipour, Abolfazl; Ashrafi Dehkordi, Korosh; Alerasoul Dehkordi, Seyed Mohammad Reza; Farzan, Mahour (International journal of biological macromolecules, 2025)
Spinal cord injury (SCI) poses significant challenges to regenerative medicine due to its limited self-repair capabilities. In this study, we engineered a biomimetic injectable hydrogel using modified chitosan and alginate biopolymers encapsulating selenium-folic acid nanoparticles (Se-FA NPs) to facilitate SCI regeneration. The hydrogel exhibited a unique porous structure attributed to the incorporation of nanofiber fragments, enhancing its biocompatibility and bioactivity. Through a series of in vitro evaluations, including cell viability assays, proliferation studies, gene expression analysis, we assessed the hydrogel's cytocompatibility and its potential for supporting neural cell growth. Our results demonstrate the promising efficacy of the hydrogel in providing a conducive microenvironment for neural tissue regeneration. Moreover, the sustained release of Se-FA NPs from the hydrogel system offers neuroprotective, antioxidative, and anti-inflammatory benefits crucial for SCI therapy. Overall, our biomimetic hydrogel biocomposites hold great potential as a therapeutic strategy for promoting spinal cord regeneration, highlighting their significance in advancing the field of regenerative medicine. [Display omitted]